Mathematical modeling of mass transfer in baromembrane processes - Ustinov, Olexandr; Zakharov, Volodymyr; Obodovych, Oleksandr (My University, 2018)
To determine the optimal modes of rational exploitation of membranes the phenomena of concentration polarization was researched. To simulate the real processes of separation, we used geometric, physical and mass-exchange characteristics of real membrane systems. Depending on the pressure, membrane characteristics and flow turbulence, the concentration polarization may exceed the value of 10, which must be taken into account in order to prevent the formation of sediment on the surface of the membrane.
Keywords: membrane; modeling; separation; concentration polarization; mas transfer; мембрани; моделювання; розділення; концентраційна поляризація; масообмін; мембраны; моделирование; разделение; концентрационная поляризация; массообмен; кафедра технологічного обладнання та комп’ютерних технологій проектування